2010
DOI: 10.1099/mic.0.039354-0
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans forms biofilms on the vaginal mucosa

Abstract: Current understanding of resistance and susceptibility to vulvovaginal candidiasis challenges existing paradigms of host defence against fungal infection. While abiotic biofilm formation has a clearly established role during systemic Candida infections, it is not known whether C. albicans forms biofilms on the vaginal mucosa and the possible role of biofilms in disease. In vivo and ex vivo murine vaginitis models were employed to examine biofilm formation by scanning electron and confocal microscopy. C. albica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
248
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(258 citation statements)
references
References 36 publications
(61 reference statements)
9
248
0
1
Order By: Relevance
“…94 Transcriptional regulation of biofilm formation has been mainly attributed to Bcr1, Tec1, and Efg1, 90 however, recent studies revealed novel transcription factors associated with this process: Ndt80, Rob1, Brg1. 95 Harriott et al 96 were the first to show using in vivo and ex vivo models of murine Candida vaginitis that C. albicans does, indeed, form Bcr1-and Efg1-dependent biofilms. Similar to other body sites, biofilms in the vagina are of major concern, as they have been implicated in immunopathology of VVC, anti-fungal treatment failures and recurrent infections.…”
Section: Pathogenesis Of Candida and Vulvovaginal Candidiasismentioning
confidence: 99%
“…94 Transcriptional regulation of biofilm formation has been mainly attributed to Bcr1, Tec1, and Efg1, 90 however, recent studies revealed novel transcription factors associated with this process: Ndt80, Rob1, Brg1. 95 Harriott et al 96 were the first to show using in vivo and ex vivo models of murine Candida vaginitis that C. albicans does, indeed, form Bcr1-and Efg1-dependent biofilms. Similar to other body sites, biofilms in the vagina are of major concern, as they have been implicated in immunopathology of VVC, anti-fungal treatment failures and recurrent infections.…”
Section: Pathogenesis Of Candida and Vulvovaginal Candidiasismentioning
confidence: 99%
“…As an initial test of filastatin in a mammalian infection model, we examined a mouse model of vulvovaginal candidiasis (VVC). This system is ideal for evaluating our compounds, because VVC infections depend on fungal morphogenesis and biofilm formation (35). This assay is medically important, because VVC affects 75% of all women at least once in their lifetimes, and because C. albicans is responsible for 85-95% of these infections (36).…”
Section: Filastatin Alters Biofilm Morphology In a Mouse Model Of Vulmentioning
confidence: 99%
“…Other Candida spp. including C. tropicalis, C. parapsilosis, and C. glabrata form ECM-containing biofilms but do not produce true hyphae [18]. Aspergillus biofilms can form both on abiotic and biotic surfaces [19].…”
Section: Fungal Biofilmsmentioning
confidence: 99%